Totalitarian Realia: Abbreviation-Based Sovietisms and the Methodology of Their Recreation in English Translations of Ukrainian Literature - Malaiko, Serhii (Vertimo studijos, 2024)
This paper explores the topic of totalitarian realia, represented by Sovietisms in the Soviet Union, from linguistic, ideological, and translation-oriented perspectives. Sovietisms can be categorized into two types: conventional and abbreviation-based. An analysis of three translations of Ukrainian Soviet-era literary works, which make extensive use of Sovietisms, identifies 139 examples. The primary focus of this paper is on abbreviation-based Sovietisms, which constitute 65.5% of the research corpus, encompass many unique linguistic phenomena, and are predominantly rendered through a domesticating approach (76%), despite the nation-narrating objectives of their translators. Based on this analysis, the key strategies for translating abbreviation-based Sovietisms into English are outlined. Additionally, an alternative strategy, termed combined renomination (calque), is proposed for foreignization-oriented nation-narrating translations involving abbreviation-based Sovietisms.
Keywords: Sovietisms; totalitarian; realia; domestication; foreignization; neutralization